Pokémon GO: Implications for Literacy in the Classroom. (1st March 2017) - Howell, Emily
Abstract: This teaching tip gives teachers practical applications of the game Pokémon GO for literacy teaching and learning. The author discusses applications of the game for teaching multimodality in upper elementary‐school classrooms. The author situates these applications in relevant theoretical perspectives as well as current literacy research.